Pemanfaatan Social Network Analysis (SNA) Untuk Analisis Pemetaan Komunikasi Pada Pegawai Bank Syariah di Jawa Tengah: Social Network Analysis - Haikal Nur Rachmanrachim Achaqie (Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2022)
Bank Syariah Mandiri is one of the sharia business units which is a work unit of the main office (parent) of conventional commercial banks which has a function as the main office of the sharia unit office or sharia branch. So far, the performance of Islamic banks is only seen from the number of assets and customers, but very rarely describes the internal conditions related to the performance of their employees. Good communication and coordination between departments is very important so that the company can run effectively and efficiently. The purpose of this research is that the company is expected to be able to analyze employee interactions through communication patterns and become policy advice in decision making, especially related to HR development. This study involved approximately 20 employees at a branch of Bank Syariah Mandiri in Central Java Province which used a social network analysis (SNA) approach. In the SNA approach, the values of density, degree centrality, closeness centrality, betweenness centrality, clicks, and visualization of relationships using a sociogram will be sought. As a result, all inter-departmental employees have good communication relationships. Based on these findings, it is necessary to solve the problem by making actors or employees who have high indegree scores to be more proactive in providing information to their colleagues so that coordination can be smooth.